Additional data on Olecryptotendipes secundus (Zorina, 2003) from Russian Far East, with a description of preimaginal stages (Diptera: Chironomidae) - Orel, Oksana V. (Zootaxa, 2022)
The male of Olecryptotendipes secundus (Zorina, 2003) is redescribed. The pupae and larvae collected from the Amur River basin are described and illustrated for the first time. The diagnosis of the genus Olecryptotendipes Zorina, 2007 is supplemented and expanded. Keys to the Far Eastern species of the genus Olecryptotentipes Zorina for adult males, pupae and larvae are given.